A Novel Image Stream Cipher Based On Dynamic Substitution - Elsharkawi, A.; El-Sagheer, R. M.; Akah, H.; Taha, H. (Engineering, Technology & Applied Science Research, 2016)
Recently, many chaos-based stream cipher algorithms have been developed. Traditional chaos stream cipher is based on XORing a generated secure random number sequence based on chaotic maps (e.g. logistic map, Bernoulli Map, Tent Map etc.) with the original image to get the encrypted image, This type of stream cipher seems to be vulnerable to chosen plaintext attacks. This paper introduces a new stream cipher algorithm based on dynamic substitution box. The new algorithm uses one substitution box (S-box) and a chaotic shuffling process. Each byte in the plain image vector is substituted using a different S-box to get the cipher image vector. This algorithm is designed to be invulnerable to chosen plaintext attacks. In addition, this algorithm is more secured compared to conventional stream cipher.